1994
DOI: 10.1063/1.110826
|View full text |Cite
|
Sign up to set email alerts
|

Surface diffusion length of Ga adatoms on (1̄1̄1̄)B surfaces during molecular beam epitaxy

Abstract: The spatial variation of the growth rate on mesa-etched GaAs (1̄1̄1̄)B substrates during molecular beam epitaxy of GaAs is measured from the period of the reflection high-energy electron diffraction (RHEED) intensity oscillation using in situ scanning microprobe RHEED. The surface diffusion length of Ga adatoms on the (1̄1̄1̄)B surface is determined from the spatial variation of the growth rate. The surface diffusion length on the (1̄1̄1̄)B surface increases as the substrate temperature is raised or the arseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…The interchange of the roles of substrate plane and sidewall between the ͑111͒A and ͑001͒ surfaces, however, might lead to different results since the effective beam fluxes are different between the substrate plane and sidewall ͑as can be understood from the difference in P Ga s and P Ga f in Table I͒, and Ga is affected by such a growth ambience. [1][2][3][4][5][6][7][8]10 The significance of the present results is that we have clearly confirmed for the first time that the experimental evidence obtained on ͑001͒ patterned substrates that Ga (111)A is longer than Ga (001) essentially originates from the crystalline anisotropy and applies to all ͑111͒A-͑001͒ systems.…”
Section: Resultssupporting
confidence: 84%
“…The interchange of the roles of substrate plane and sidewall between the ͑111͒A and ͑001͒ surfaces, however, might lead to different results since the effective beam fluxes are different between the substrate plane and sidewall ͑as can be understood from the difference in P Ga s and P Ga f in Table I͒, and Ga is affected by such a growth ambience. [1][2][3][4][5][6][7][8]10 The significance of the present results is that we have clearly confirmed for the first time that the experimental evidence obtained on ͑001͒ patterned substrates that Ga (111)A is longer than Ga (001) essentially originates from the crystalline anisotropy and applies to all ͑111͒A-͑001͒ systems.…”
Section: Resultssupporting
confidence: 84%
“…3. These fits used the adatom diffusion lengths shown in Table 1, which are consistent with typical adatom diffusion lengths measured elsewhere [24,25]. In addition, to successfully fit the model to the data, it was necessary to assume that growth by bulk Fig.…”
Section: Discussionmentioning
confidence: 94%
“…32 In our case, the annealing temperature was 550 C, so that strong Ga atoms surface diffusion is expected. Meanwhile, it has been reported that (1) Au may attract a large amount of Ga even at 250 C, 33 and (2) the maximum diffusion length of Ga atoms on GaAs {111} B surface has been estimated at 5 lm at 500 C, 34 so that a significant amount of Ga atoms can be attracted towards to the Au nanoparticles at the annealing temperature of 550 C. It should be noted that, in our study, the Au was deposited on the GaAs buffer layer within the MBE system, the surface of GaAs buffer layer must be clear from possible oxidation, which makes the surface diffusion of Ga atoms much easier. To address the …”
Section: Au Impact On Gaas Epitaxial Growth On Gaas (111) B Substratementioning
confidence: 99%